Shared Metabolic–Proteinopathy Axis in Alzheimer's Disease and Parkinson's Disease: Evidence for a Convergent but Not Identical Disease Spectrum - Shun‐yu Yao; Miao‐qiao Du; Lan‐xin Lin; Xu‐hui Kang; Dai‐yi Jiang; Yong Peng (AGING MEDICINE, 2026)
ABSTRACT Alzheimer's disease (AD) and Parkinson's disease (PD) are the two most prevalent neurodegenerative disorders globally and have long been classified as clinically and pathologically distinct syndromes. AD is defined by amyloid‐β (Aβ) plaques and tau‐positive neurofibrillary tangles, whereas PD is characterized by α‐synuclein aggregation and progressive degeneration of nigrostriatal dopaminergic neurons. However, mounting evidence has blurred the traditional boundaries between these disorders, revealing extensive overlaps in pathogenic cascades, clinical phenotypes, and epidemiological risk factors. In this review, we propose an integrated mechanistic framework in which AD and PD represent distinct yet partially overlapping disorders along a convergent neurodegenerative spectrum, unified by a core metabolic–proteinopathy axis. We highlight cerebral insulin resistance and impaired brain glucose metabolism as pivotal upstream triggers that initiate a cascade of pathological events, including mitochondrial dysfunction, energy depletion, oxidative stress, chronic neuroinflammation, and disrupted proteostasis. These disturbances collectively drive aberrant folding and aggregation of Aβ, tau, and α‐synuclein, establishing a mechanistic link between systemic metabolic dysregulation and region‐selective neuronal vulnerability. We synthesize evidence from molecular studies, preclinical models, clinicopathological analyses, neuroimaging, and longitudinal epidemiological surveys to delineate the extent and limitations of mechanistic convergence. We also emphasize consistent divergences between AD and PD, including distinct patterns of neuroanatomical involvement, dominant clinical presentations, pathological propagation trajectories, and genetic architectures. Epidemiological data confirm that Type 2 diabetes and insulin resistance are associated with elevated risk of both AD and PD. Moreover, antidiabetic agents such as GLP‐1 receptor agonists exhibit convergent neuroprotective efficacy in preclinical and early clinical investigations, supporting metabolic modulation as a promising cross‐disease therapeutic strategy. Despite shared downstream pathways and therapeutic targets, AD and PD retain unique pathological signatures and clinical progression patterns. This review provides a balanced, evidence‐based interpretation of the AD–PD relationship, highlighting partial pathogenic convergence driven by metabolic dysfunction while affirming their identities as distinct disorders. The proposed metabolic–proteinopathy framework advances mechanistic understanding and informs the development of novel disease‐modifying therapies targeting shared upstream pathways.